Prevalence of gallstone disease in Africa: a systematic review and meta-analysis - Seid Mohammed Abdu; Ebrahim Msaye Assefa (BMJ Open Gastroenterology)
Objective Gallstone disease is a prevalent global health issue, but its impact in Africa remains unclear. This study aims to summarise and synthesise available data on the prevalence of gallstone disease across populations in Africa.Design Systematic review and meta-analysis, reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines.Data sources PubMed, Google Scholar, Hinari, and African Journal Online were searched, from 2000 up to 31 December 2023.Eligibility criteria The review included all observational studies that reported the prevalence of gallstone disease and were published in English.Data extraction and synthesis Two independent reviewers extracted data and assessed the risk of bias using the Joanna Briggs Institute (JBI) tool. Data were pooled using a random-effects and inverse variance method, with 95% confidence intervals (95% CI) calculated. Heterogeneity was assessed using the Cochran Q statistic and quantified with the I² statistic.Results A total of 260 studies were identified from electronic databases, with 10 meeting the inclusion criteria. The combined prevalence of gallstone disease was 17% (95% CI 9% to 24%), but with high statistical heterogeneity (I²=99.9%). Only 8 of the 10 included studies provided prevalence data by sex, showing notably higher rates in females (15.3%) compared with males (3.7%).Conclusion The study reveals a pooled gallstone disease prevalence of 17% in Africa, with higher rates in females. However, the significant heterogeneity, the lack of data from most countries and an imbalance in data from other countries, the diverse study populations, and the limited number of studies necessitate cautious interpretation. Future policies and interventions should prioritise reducing gallstone disease, particularly in females, while addressing the variability in data sources.PROSPERO registration number CRD42024503530.